1975
DOI: 10.1111/j.1471-4159.1975.tb12239.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylic Acid‐containing Rna From Rat Brain Synaptosomes

Abstract: Abstract— Synaptosomal RNA of rat brain was labelled in vivo by intracranial injection of tritiated uridine. The change in the specific activity of this material with time was similar to that of polysomal RNA. The percent of the radioactive synaptosomal RNA which bound to oligo(dT)‐cellulose columns decreased with time after intracranial labelling. The percent of the total synaptosomal RNA which bound to oligo(dT)‐cellulose was greater than that of polysomes. The length of the polyadenylate (poly(A)) sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The in vitro studies carried out with both brain and sciatic nerve indicate that tissues of younger animals appear to synthesize RNA possessing a greater proportion of poly(A)+ sequences than did RNA synthesized in tissues of post-hatching chicks ( Table 3). These results are similar to those obtained for rat and mouse brain in vitro and in vivo (DeLarco and Guroff, 1972;Banks and Johnson, 1973;DeLarco et al, 1975;Berthold and Lim, 1976~). However, in vivo results carried out with brain tissue in the present investigation indicate a different trend ( Table 4).…”
Section: Discussionsupporting
confidence: 90%
“…The in vitro studies carried out with both brain and sciatic nerve indicate that tissues of younger animals appear to synthesize RNA possessing a greater proportion of poly(A)+ sequences than did RNA synthesized in tissues of post-hatching chicks ( Table 3). These results are similar to those obtained for rat and mouse brain in vitro and in vivo (DeLarco and Guroff, 1972;Banks and Johnson, 1973;DeLarco et al, 1975;Berthold and Lim, 1976~). However, in vivo results carried out with brain tissue in the present investigation indicate a different trend ( Table 4).…”
Section: Discussionsupporting
confidence: 90%
“…Synthesis of synaptosomal RNA was examined in young rats after the intracranial injection of [ 3 H]uridine and [ 3 H]adenosine (69). At the earliest time examined (1 h), the specific activity of synaptosomal RNA was approximately half that of mitochondrial RNA and one-fourth that of polysomal RNA.…”
Section: Synaptosomal Extramitochondrial Rnamentioning
confidence: 99%
“…In early studies (14), cell body mitochondria and intrasynaptosomal mitochondria from rat brain were shown to contain similar concentrations of DNA (6.3 g/mg protein) and RNA (12-13 g/mg protein), but higher concentrations of RNA were present in synaptosomal membrane fractions (up to 21 g/mg protein). In later studies, extramitochondrial synaptosomal RNA was identified as rRNAs and 4S RNA that were consistently attributed to contaminating elements (59,69,89,211). Nonetheless, in addition to mitochondrial RNAs and typical cytoplasmic rRNA (18S, 28S) and small RNA (4S, 5S), the synaptosomal fraction of adult rat brain contained two RNA components that were absent in mitochondrial and microsomal fractions (59, 60).…”
Section: B Vertebrate Nerve Endingsmentioning
confidence: 99%
See 2 more Smart Citations